Geological objects and structures in 3D: observation, interpretation and building of 3D Models - Stawikowski, Wojciech (Geologos, 2024)
Geological objects and structures in 3D: observation, interpretation and building of 3D Models, by D. Frizon de Lamotte, P. Leturmy, P. Souloumiac & A. Frizon de Lamotte, 2021. CRC Press, London, 138 pages. Paperback: price GBP 39.09, ISBN 978-0367497507